2005
DOI: 10.1186/1743-422x-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of macrophage functions by sheeppox virus provides clues to understand interaction of the virus with host immune system

Abstract: Background: Poxviruses encode a range of immunomodulatory genes to subvert or evade the challenges posed by the innate and adaptive immune responses. However, the inactivated poxviruses possessed immunostimulating capacity and were used as a prophylactic or metaphylactic application that efficiently reduced susceptibility to infectious diseases in different species. This fact is intensively studied in different genera of poxviruses. However, little is known about the basic mechanisms adopted by sheeppox virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Among the tested cytokines, the expressions of TNFα, IL-15, and IL-10 were all significantly upregulated, suggesting that they may play an essential role in SPPV infections. A similar increase in IL-10 expression following SPPV infection in vivo has been reported ( 31 ). IL-10 is a critical anti-inflammatory cytokine secreted by monocytes following their infection with pathogens, and increased production of IL-10 following infection by other poxviruses has been previously reported ( 25 , 32 ).…”
Section: Discussionsupporting
confidence: 83%
“…Among the tested cytokines, the expressions of TNFα, IL-15, and IL-10 were all significantly upregulated, suggesting that they may play an essential role in SPPV infections. A similar increase in IL-10 expression following SPPV infection in vivo has been reported ( 31 ). IL-10 is a critical anti-inflammatory cytokine secreted by monocytes following their infection with pathogens, and increased production of IL-10 following infection by other poxviruses has been previously reported ( 25 , 32 ).…”
Section: Discussionsupporting
confidence: 83%
“…Humoral response was found to be acceptable after using 10 4.0 TCID50 of RM65 SPP vaccine [ 40 ]. Interestingly, it was found that in spite of vaccination, the local immune evasion strategy adopted by capripoxviruses locally alleviates the host’s immune response to allow the virus to replicate at the site of entry [ 41 ].…”
Section: Discussionmentioning
confidence: 99%